2009
DOI: 10.1111/j.1365-2095.2008.00632.x
|View full text |Cite
|
Sign up to set email alerts
|

A dietary energy level of 14.6 MJ kg−1and protein-to-energy ratio of 20.2 g MJ−1results in best growth performance and nutrient accretion in silver barbPuntius gonionotusfingerlings

Abstract: Five iso-nitrogenous (300 g protein kg )1 diet) and iso-lipidic (80 g kg )1 diet) semi-purified experimental diets with variable energy levels of 10.5 (D-1), 12.5 (D-2), 14.6 (D-3), 16.7 (D-4) and 18.8 (D-5) MJ kg )1 diets were fed to Puntius gonionotus fingerlings (average weight 1.79 ± 0.02 g) in triplicate groups (15 healthy fishes per replicate) for a period of 90 days to assess the optimum dietary energy level and protein-to-energy ratio (P/E). Fifteen flow-through cement tanks of 100 L capacity with a fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 71 publications
3
24
0
Order By: Relevance
“…It was also reported that when the diet was deficient of non‐protein energy, the protein was used for energy rather than the growth (Kim, Wang, Choi, Park & Bai ; Mohanta et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…It was also reported that when the diet was deficient of non‐protein energy, the protein was used for energy rather than the growth (Kim, Wang, Choi, Park & Bai ; Mohanta et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Fish, like other animals, control their feed intake to meet their energy requirements (Kaushik & Medale ), but excessive energy in the diets is undesirable because it may reduce feed intake, and results in growth and feed efficiency depression because of lack of necessary nutrients such as protein for normal growth (Mohanta et al . ). In the present study, feed intake was affected by dietary protein level and lipid level, and feed intake of fish fed the 80 g kg −1 lipid diet was significantly lower than that of fish fed the 160 g kg −1 lipid diet at 400 g kg −1 protein, this finding agrees with other studies (McGoogan & Gatlin ; Kim & Lee ; Mohanta et al .…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, feed intake was affected by dietary protein level and lipid level, and feed intake of fish fed the 80 g kg −1 lipid diet was significantly lower than that of fish fed the 160 g kg −1 lipid diet at 400 g kg −1 protein, this finding agrees with other studies (McGoogan & Gatlin ; Kim & Lee ; Mohanta et al . ). However, no significant differences in daily feed intake were observed between lipid levels in the 450, 500 and 550 g kg −1 protein diet, feed intake seemed to adjust to protein intake because of the dietary fishmeal levels.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Knowledge of performance of early silver barb fry at different salinities would likely benefit the aquaculture industry since they are important commercially throughout Southeast Asia and India, with aquaculture production for human consumption increasing from approximately 90,000 tonnes (t) in 2005 to over 160,000 t in 2014 (FAO, ). This is largely due to their relative ease of spawning in captivity, rapid growth rate and high market demand, leading to increased research for aquaculture (Mohanta, Mohanty, Jena, & Sahu, ; Mohanta, Mohanty, Jena, & Sahu, ; Mohanta, Mohanty, Jena, Sahu, & Patro, ). The objective of this study was to assess the effect of different salinities on the survival, growth and glycogen distribution in the early fry silver barb, Barbodes gonionotus .…”
Section: Introductionmentioning
confidence: 99%